(untitled) (Czech Journal of International Relations, 2000)
For Russia last year was at least as unprecedented as 1991 when the Soviet Union broke up and when a new, independent Russia emerged during the attempt at staging a coup, led by the political star of the time, Boris Yeltsin. This year it was not a matter of merely changing the President but, above all, of preserving or transforming the general course along which Russia is moving. That is why practically Russia’s entire internal political life during the past two years has been marked by the search for a suitable presidential successor. In his essay, the author not only highlights the biography of Vladimir Putin, but concentrates mainly on the circumstances which prompted his election as the new Russian President. From the moment of his appointment as Prime Minister, Putin skilfully exploited all his earlier experiences to his own advantage. An inseparable part of his image and his crucial pre-election trump card was his harsh attitude towards Chechnya. Thanks to the support he received in the 1999 parliamentary elections, he won to his side the Union of right-wing forces and the bloc of governors, Jedinstvo. And as a result of Yeltsin’s early resignation (influenced by his so-called family) he succeeded in speeding up and shortening the presidential campaign and in becoming the interim President. However, in the course of the election campaign, virtually no one was given any concrete information about Putin’s programme as a future President, and as a result experts in Russian affairs throughout the world as well as Putin’s fellow citizens still wonder: What is to be expected from the present Russian President? Apart from Putin’s personality, the author naturally turns his attention also to the other, less successful candidates – Gennadij Zyuganov and Grigorij Yavlinski. The second part of the essay is devoted to the prognosis as to what can be expected of Putin as the new Russian President in the economic sphere as well us in his domestic and foreign policy.